A Study of the relationship between the base oil price and profitability of refinery companies - CHOI, You Mi (KDI School, 2018)
This paper analyzes the relationship between the base oil price, announced by international pricing organizations, and the profitability of refinery companies. Specifically, this study examines the relationship between the Group II 150N and 500N base oil price and the profitability of major Korean companies in the 150N and 500N market. The study finds that the operating profit ratios of the Korean companies are closely related to changes in the 150N/500N base oil price.
Thesis(Master) --KDI School:Master of Development Policy,2018